Disturbed functional connectivity and topological properties of the frontal lobe in minimally conscious state based on resting-state fNIRS - Chen, Hui; Miao, Guofu; Wang, Sirui; Zheng, Jun; Zhang, Xin; Lin, Junbin; Hao, Chizi; Huang, Hailong; Jiang, Ting; Gong, Yu; Liao, Weijing (Frontiers in Neuroscience, 2023)
Background: Patients with minimally conscious state (MCS) exist measurable evidence of consciousness. The frontal lobe is a key part of the brain that encodes abstract information and is closely related to conscious state. We hypothesized that the disturbance of the frontal functional network exists in MCS patients. Method: We collected the resting-state functional near-infrared spectroscopy (fNIRS) data of fifteen MCS patients and sixteen age- and gender-matched healthy controls (HC) The Coma Recovery Scale-Revised (CRS-R) scale of MCS patients was also composed. The topology of the frontal functional network was analyzed in two groups. Results: Compared with HC, the MCS patients showed widely disrupted in functional connectivity in the frontal lobe, especially in the frontopolar area and right dorsolateral prefrontal cortex. Moreover, the MCS patients displayed lower clustering coefficient, global efficiency, local efficiency, and higher characteristic path length. In addition, nodal clustering coefficient and nodal local efficiency in the left frontopolar area and right dorsolateral prefrontal cortex were significantly reduced in patients with MCS. Furthermore, the nodal clustering coefficient and nodal local efficiency in the right dorsolateral prefrontal cortex were positively correlated to auditory subscale scores. Conclusions: This study reveals that MCS patients' frontal lobe functional network is synergistically dysfunctional. And the balance between information separation and integration in the frontal lobe is broken, especially the local information transmission in the prefrontal cortex. These findings help us to understand the pathological mechanism of MCS patients better.